STUDIES ON KINETICS OF DIMETHYL CARBONATE SYNTHESIS BY HOMOGENEOUS TRANSESTERIFICATION - Haznan Abimanyu (Jurnal Kimia Terapan Indonesia, 2009)
A comprehensive kinetic study on dimethyl carbonate synthesis by transesterification of ethylene carbonate with methanol has been conducted. An alkali base metal (KOH) was used as catalyst in the synthesis of DMC and its catalytic ability was investigated in term of kinetics. The reaction orders, the activation energy and the rate constants were determined for both forward and backward reactions. The reaction is reversible and the equilibrium rate constant wasestimated to be 135.77exp(-16542.4/RT).Keywords : dimethyl carbonate synthesis, transesterification reaction, kinetic study on DMC synthesis